Identity "Duality" in the context of historical-political marginalization (on the example of H. Asatryan) - Sargsyan, Armen (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
The article is devoted to the analysis of the phenomenon of identity duality in the context of its connection with historical and political marginalization, based on the example of Asatryan’s philosophical heritage. Although the Armenian thinker did not use the terms duality of identity and marginalization, in his works he discussed the issue of the ethnopsychological portrait of Armenians in the context of the connection between the aforementioned phenomena. Based on the example of Asatryan, it is substantiated that the duality of Armenian identity will become an obstacle to his historical progress if he refuses spiritual renewal, acceptance of new truths, goal-setting and the will to achieve it.